The Study of Extreme Flood Vulnerability Spatial Distribution in Chinese Mainland - Lili Guan; Jianni Yi; Wei Li (Engineering Reports, 2025)
ABSTRACT The study of the spatial distribution of vulnerability to extreme floods (EF) is of great practical significance. Due to the vast territory of China and the great differences in population, social structure, economy, and natural environment between different provinces, the vulnerability to EF disasters varies greatly. This study integrates life, economic, environmental, and social influences, with the combination of the cloud‐model method and variable fuzzy theory to establish a vulnerability assessment model. Ranking the calculation results of Chinese mainland 31 provincial regions, it shows that 80% of China's regions are rated medium to severe grades. Developed economy and high population density are the main reasons for the high vulnerability. The vulnerability evaluation model and spatial distribution ideas proposed in this paper provide an insightful research basis for risk decision‐making and risk management.